Electrochemical, mechanical, and antibacterial properties of the AZ91 Mg alloy by hybrid and layered hydroxyapatite and tantalum oxide sol–gel coating - Albayrak, Sevda; Gül, Canser; Emin, Nuray; Gökmen, Uğur; Karakoç, Halil; Uzun, Arif; Çinici, Hanifi (Walter de Gruyter GmbH, 2023)
Abstract The corrosion and bacterial behavior of AZ91 magnesium alloy coated with sol–gel-deposited amorphous tantalum oxide and hydroxyapatite have been investigated. The objective was to assess the potential suitability of AZ91 for permanent prosthesis applications. The coatings were applied in layered and hybrid configurations and characterized using various techniques including X-ray diffractometry, Fourier transform infrared spectroscopy, scanning electron microscopy/energy dispersive spectrometry, and drop analyses. The antibacterial properties were evaluated through interactions with Staphylococcus aureus and Escherichia coli strains. Mechanical properties and adhesion were determined via linear scratch tests, and electrochemical corrosion tests were conducted in different media. The release of aluminum ions from the samples in Dulbecco’s Modified Eagle’s Medium was monitored over 28 days. The findings revealed that the amorphous tantalum oxide coating, particularly in combination with hydroxyapatite, improved antibacterial properties and positively influenced corrosion and scratch resistance. The layered and hybrid coatings demonstrated the highest corrosion resistance. The release of aluminum ions remained within acceptable levels in the tested medium. Overall, the study provides valuable insights into the potential of sol–gel coatings on AZ91 for prosthetic applications, considering antibacterial behavior, corrosion resistance, and aluminum release.
Keywords: 13. Climate action